Serological evidence of human infection with avian influenza A(H7N9) virus: a systematic review and meta-analysis - Wang, W; Chen, X; Wang, Y; Lai, S; Yang, J; Cowling, BJ; Horby, PW; Uyeki, TM; Yu, H (Oxford University Press, 2020)
Background The extent of human infections with avian influenza A(H7N9) virus, including mild and asymptomatic infections, is uncertain. Methods We performed a systematic review and meta-analysis of serosurveys for avian influenza A(H7N9) virus infections in humans published during 2013–2020. Three seropositive definitions were assessed to estimate pooled seroprevalence, seroconversion rate, and seroincidence by types of exposures. We applied a scoring system to assess the quality of included studies. Results Of 31 included studies, pooled seroprevalence of A(H7N9) virus antibodies from all participants was 0.02%, with poultry workers, close contacts, and general populations having seroprevalence of 0.1%, 0.2%, and 0.02%, respectively, based on the World Health Organization (WHO)—recommended definition. Although most infections were asymptomatic, evidence of infection was highest in poultry workers (5% seroconversion, 19.1% seroincidence per 100 person-years). Use of different virus clades did not significantly affect seroprevalence estimates. Most serological studies were of low to moderate quality and did not follow standardized seroepidemiological protocols or WHO-recommended laboratory methods. Conclusions Human infections with avian influenza A(H7N9) virus have been uncommon, especially for general populations. Workers with occupational exposures to poultry and close contacts of A(H7N9) human cases had low risks of infection.